ANN and data mining approaches to select student category in ITS - Dey A.; Mishra R.B.; Pal K.C. (My University, 2025)
Data mining Methods have widely used to classification and categorization problems. It requires the categorization of the student on the basics of their performance. In this work an application of the data mining technique such as: Decision Tree (DT), Classification and Regression Trees (C&RT algorithm) have been used in the data set for the categorizing the student as high, medium and low. It's important to use (ANN) because this is a method by which students are categorized through cognitive input and behavioral input. We have used a data mining method Classification and Regression Trees (C&RT) to categorize the students in different category based on their cognitive and behavioral parameter. © 2013 Springer-Verlag.